Common law and modern society : keeping pace with change - Arden, Mary (Oxford : Oxford University Press, 2016)
Law is a lasting social institution, but it must also be responsive to change. In this volume Mary Arden draws upon her experience to examine how judge-made law adapts to the evolving demands of society, how law reform works in practice, and the future of the judiciary in our diverse modern culture.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 27, 2016).
Keywords: Common law; Sociological jurisprudence; Law